(untitled) (Third Sector Social Economic Review, 2024)
In this study, the ability of the parameters, used in different company valuation methods to explain the changes in market value of manufacturing sector companies in the BIST100 index, is examined through an empirical analysis. Based on the IPOs in Borsa Istanbul in 2022-2023; the study uses the parameters utilized in the Discounted Cash Flows (FCFE, FCFF), Market Multiples (EV/Sales, EV/EBITDA) and as an alternative model, Residual Income (RI) method. The empirical analysis reveals that FCFE, FCFF, RI, Net Sales and EBITDA parameters are successful in explaining the changes in the market value of companies, and the model with Net Sales, RI and FCFE variables is the most explanatory model. Moreover, Net Sales was found to have a higher impact than the others and Residual Income was also found to have a noteworthy impact. Therefore, increasing the weight of the “EV/Net Sales” multiple within the market multiples method and using more than one valuation methods together, including Residual Income method may contribute to reaching more accurate results.